2014
DOI: 10.1177/0734242x14550739
|View full text |Cite
|
Sign up to set email alerts
|

Variation in organic matter characteristics of landfill leachates in different stabilisation stages

Abstract: This study investigates the effect of landfill age on landfill leachate characteristics; two aspects are focused here. One is ultraviolet absorbance at 254 nm (UV(254)) property, as the discharge of landfill leachates to publically owned treatment works can cause interference with UV(254) disinfection. The other is biorefractory organic nitrogen in leachates, as it can contribute to effluent nitrogen making it difficult to meet stringent effluent nitrogen regulations. To study variation in UV(254)-absorbing or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The colloidal organic matter refers to the humic-like 26/39 substances which are more settleable and can be destabilized much easily than short chain organic acids. Studies have shown that normal leachate and concentrated leachate have different proportions of humic-like substances, and humic-like substance fraction is higher in normal leachate than concentrated leachate (Gawande, 2018;Gupta et al, 2014b;Iskander et al, 2018;Zhao et al, 2013a). In this study, it is shown that organic matter in normal leachate is humic-like substances dominated, while concentrated leachate short chain organic acids dominated.…”
Section: /39mentioning
confidence: 47%
“…The colloidal organic matter refers to the humic-like 26/39 substances which are more settleable and can be destabilized much easily than short chain organic acids. Studies have shown that normal leachate and concentrated leachate have different proportions of humic-like substances, and humic-like substance fraction is higher in normal leachate than concentrated leachate (Gawande, 2018;Gupta et al, 2014b;Iskander et al, 2018;Zhao et al, 2013a). In this study, it is shown that organic matter in normal leachate is humic-like substances dominated, while concentrated leachate short chain organic acids dominated.…”
Section: /39mentioning
confidence: 47%
“…ASFV can be transmitted by direct or indirect contact between infected animals, infected pig products, or infected fomites, such as transport vehicles (26,27). Organic materials such as soil and manure can interfere with disinfectants (HPCI and COAs) (28). Based on the above results, we recommend that the ground and equipment of pig farms were thoroughly washed and then disinfected.…”
Section: Discussionmentioning
confidence: 99%
“…e clay mineral membranes are exposed to various chemical, biological, and physical stresses, and they are influenced by the subsequent leachate [16][17][18][19][20][21]. To evaluate the consistency of these membranes, it is important to examine their chemical compatibility with the different fluids or the leachate to which they are subjected [22].…”
Section: Introductionmentioning
confidence: 99%